UPPER RESPIRATORY TRACT INFECTION EDUCATION AT MUHAMMADIYAH CLINIC OF SUGIO LAMONGAN - Munaa, Nihayatul; Saputra, Muhamad Ganda (Universitas Muhammadiyah Lamongan, 2024)
Background: According to WHO upper respiratory tract infection (URTI) is an infectious disease of the upper respiratory tract which can cause a wide spectrum of disease ranging from mild infection to severe and deadly disease, depending on the causative pathogen, host factors and environmental factors. Environment-based diseases are still the leading cause of death in Indonesia. URTI disease in Indonesia is in the top 10 list of diseases in hospitals. URTI causes are related to the environmental conditions where the patient lives. This community service activity aims to increase the knowledge and understanding of patients and families of patients at the Muhammadiyah Sugio Clinic how to recognize risk factors for URT disease transmission. Method: The activity was carried out on Friday, September 23, 2022. Results: The results of the community service activities obtained that of the 10 patient families who participated in the activity, 50% were aware of URTI disease and 25% understood how to prevent and treat URTI disease. Conclusion: it can be conclude that this community service program has increase the knowledge of respiratory disease among inpatient at sugio muhammadiyah clini Lamongan